Chemical characterization and bioactivity of Trichosanthes dioica edible shoot extract - Zilani, Md. Nazmul Hasan; Uddin, Shaikh Jamal; Hossain, Hemayet; Hazni, Hazrina; Shilpi, Jamil A.; Hossain, Md. Golam (Springer Verlag (Germany), 2018)
Present investigation was aimed to evaluate the traditional use of edible part of soft shoots of Trichosanthes dioica Roxb. (Cucurbitaceae) as an antidiabetic in mice model. In addition, antioxidant activity and chemical profiling of this plant part were also performed to support its observed activity. The extract was subjected to oral glucose tolerance test in normal and alloxan induced diabetic mice to explore its antihyperglycemic activity. Antioxidant capacity was analyzed by a number of in vitro assays. Quantification of bioactive polyphenols was done by HPLC. Liquid Chromatography coupled with Mass Spectrometry (LCMS) was used to identify chemical constituents present in the extract. Total polyphenol and flavonoids content were found in significant quantity. In DPPH radical scavenging assay the IC50 value of the extract was found to be 148.62 µg/mL. Reducing power of the extract was comparable with that of butylatedhydroxytoluene (BHT). HPLC analysis indicated that quercetin, rutin, p-coumaric acid and kaempferol were the major bioactive polyphenols present in the extract. Further chemical profiling using LCMS analysis was identified a total of nine compounds with different chemical classes. In OGTT, extract (400 mg/kg BW) showed a 31.13% decrease (p < 0.05) in blood glucose levels at 30 min compared to the normal control. In alloxan induced diabetic mice the extract at the doses of 200 mg and 400 mg/kg, showed significant decrease (p < 0.05) of blood glucose level compared to diabetic control. The extract showed oral glucose tolerance potential and antioxidant capacity which might be due to the presence of different compounds such as quercetin, rutin, kaempferol, oleanolic acid, β-sitosterol. The results support the scientific basis of it ethnobotanical uses in traditional medicinal practices of Bangladesh.